The emergence of whistleblower protection in New Zealand : an exploratory study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Human Resource Management at Massey University - McErlane, Vincent Gerard (Massey University, 1995)
The address of wrongdoing in society is seen as an important goal of government. Yet uncertainty exists as to the most effective and appropriate means to achieve this goal. One recent method that is believed to assist in this is the encouragement of whistleblowing through protective legislation. Leading this development has been the United States of America, with more recent legislation enacted in various jurisdictions in Australia. As a result of recent events here in New Zealand, whistleblower legislation has been proposed. In the present study, a broad examination of the research literature on whistleblowing is presented. This examination provides a foundation whereby legal mechanisms of whistleblower protection in the United States and Australia are examined. Having identified these jurisdictions' more notable points, the New Zealand Bill is considered. Analysis of New Zealand's existing and proposed mechanisms of protection are highlighted and compared with overseas' protections. Findings from this comparison identify significant strengths and weaknesses inherent to the Bill. In particular, this study finds that the New Zealand Bill is likely to suffer from the same shortcomings as those experienced in the United States and Australia. In response to these shortcomings, the study turns to focus on internal mechanisms that may be employed at the organisational level. This exploratory study provides a solid frame of reference in analysing the emergence of whistleblower protection in New Zealand, and lays the foundation for more extensive research to be conducted in the future.
Keywords: Whistle blowing; Whistleblowers Protection Bill 1994; New Zealand; Law and legislation